CONVERSION OF FOREIGN COMPANIES ACCOUNTS IN THE ACCOUNT CONSOLIDATION PROCESS IN ROMANIA UNDER THE CLOSING RATE METHOD - Mariana BANUTA; Mihaela GADOIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The article approaches a topical theme of debate both in the professional academic environment and especially in the economic practice, i.e. the manner of converting the accounts of foreign companies in the account consolidation process, in Romania. We analyse the conditions of applying the accounting regulations related to the consolidation of accounts, in Romania, focusing on the manner of converting the accounts of the foreign companies according to Order no. 1802/2014 approving the accounting regulations on individual annual financial statements and consolidated annual financial statements and to the International Financial Reporting Standards (IFRS). We focused on the presentation of the practical method of applying the conversion of the accounts of the foreign companies according to the closing rate method, because irrespective of the accounting referential applied by the parent company for consolidation, this method occurs in the pre-consolidation stage, if the group leader has affiliates abroad, and the individual financial statements of the companies in the consolidation perimeter have different disclosure currencies.